Exploring Academic Atmospheres in IAIN Kediri Inspiring from State University in Malaysia - Abdullah, Mukhammad (International Journal of Advanced Science and Technology, 2020)
This article explores the academic atmospheres of universities in Indonesia and Malaysia, comparing university missions, services and management supports. Institut Agama Islam Negeri (IAIN) Kediri, East Java, Indonesia and Universitas Teknologi Malaysia (UTM), Malaysia were evaluated in this study. Comparison is laid in the management process the universties serve to achieve the academic attainments and supports to teaching staffs as the core human resources in the university to operate the management where the academic atmospheres are immensely created and built. Restrictions appear, however, in that this study does not mean to compare the universities apple to apple, rather it portrays general academic attitudes and attainments in the light of education management that the universities have accomplished. Academic atmospheres in the university are the embodiment of leadership that manifest teaching performance, student management, curriculum, and supports to academic faculty in enhancing researches in the international linkages and publications. Content analysis was used as the research design, involving data from the results of observation, interview and document analyses.  The study revealed that academic atmospheres in IAIN Kediri indicated standard performance on three ultimate obligations, teaching, research and community outreach, the management and leadership of which are on going to increase.  Lacking of internationalization programs, however, IAIN Kediri developed its basis as Islamic center. In addition, UTM has achieved international statuses in its performances and standards. This implies that IAIN Kediri should increase its status to be university level, create the curriculum body and academic attainments in the international standard.